O impacto sociocultural do uso da internet em um grupo de pessoas idosas - Reis, Adriana Araújo (2012)
The new technologies of information and communication are of paramount importance for the development of society, especially the internet that offers its users a wide variety of attractions that are considered extremely relevant for society and fundamental to socio-cultural activities in various sectors, besides its importance in interpersonal relationships, regardless the age group. This dissertation aimed to investigate the social impact of internet use in a group of elderly people, observing changes in the social environment that occur with older people using the internet. For the study, was used a qualitative approach, held in semi-structured interviews with ten elderly people who used the internet and who were enrolled in a course at the Open University to Maturity of PUC/SP. The reflection of the data collected was based on plausible theoretical frameworks of our literature about aging, considering the theoretical categories of analysis that contributed to the discussion on the effect of the internet in everyday life of the elderly. The results indicate that internet s use has contributions in the practical day-to-day, socialization, the discovery of new knowledge and information for older people. The handling of the Internet by elderly provides them greater social participation, implying in their personal and social life